Interpersonal Factors Are Associated with Lower Therapist Adherence in Cognitive–Behavioural Therapy for Panic Disorder. (17th April 2015) - Zickgraf, Hana F.; Chambless, Dianne L.; McCarthy, Kevin S.; Gallop, Robert; Sharpless, Brian A.; Milrod, Barbara L.; Barber, Jacques P.
Abstract : Objective: The contributions of disorder severity, comorbidity and interpersonal variables to therapists' adherence to a cognitive–behavioural treatment (CBT) manual were tested. Method: Thirty‐eight patients received panic control therapy (PCT) for panic disorder. Trained observers watching videotapes of the sixth session of a 24‐session protocol rated therapists' adherence to PCT and their use of interventions from outside the CBT model. Different observers rated patients' behavioural resistance to therapy in the same session using the client resistance code. Interview measures obtained before treatment included the Panic Disorder Severity Scale, the anxiety disorders interview schedule for Diagnostic and Statistical Manual of Mental Disorders (DSM)‐IV and the structured clinical interview for DSM‐IV, Axis II. Questionnaire measures were the anxiety sensitivity index at intake, and, at session 2, the therapist and client versions of the working alliance inventory—short form. Results: The higher the patients' resistance and the more Axis II traits a patient had, the less adherent the therapist. Moreover, the more resistant the client, the more therapists resorted to interventions from outside the CBT model. Stronger therapist and patient alliance was also generally related to better adherence, but these results were somewhat inconsistent across therapists. Pretreatment disorder severity and comorbidity were not related to adherence. Conclusions: Interpersonal variables, particularly behavioural resistance to therapy, are related to therapists' ability to adhere to a treatment manual and to their use of interventions from outside of the CBT model. Copyright © 2015 John Wiley & Sons, Ltd. Key Practitioner message: Patients' behavioural resistance to therapy may make it more difficult for cognitive–behavioural clinicians to adhere to a structured treatment protocol and more likely for them to borrow interventions from outside the CBT model. Patients' Axis II traits may make adherence to treatment CBT protocol more difficult, although whether this is true varies across therapists. Therapists' adherence to a structured protocol and borrowing from outside of the CBT model do not appear to be affected by disorder severity or Axis I comorbidity.